AN INFANT OF “ELITE” WARI IN PUCLLANA: RESULTS OF THE UNWRAPPING PROCESS - PAZ FLORES, Gladys (2021)
The latest research carried out in the Pucllana Ceremonial Center, have revealed the existence of 82 tombs belonging to a cemetery of the Wari period located between the IV and VI Platform of the Great Pyramid. In the 2008 season, the Huaca Pucllana Research, Conservation and Valorization Project (PICPVHP) led by Dr. Isabel Flores Espinoza, excavated an individual funerary context belonging to an infant that retained most of its elements in situ as the structure, the bale and offerings. In the 2011 season, the unbundling process was carried out by a multidisciplinary team among archaeologists, bioanthropologists and curators of which are exposed in this publication; the methodology, characteristics and composition of the bale and the results in order to a better understanding of Wari funerary practice for infants of the elite social class in the Central Coast area.